Indigenous Languages Dictionaries and Pedagogical Lexicography - Fargetti, Cristina Martins [UNESP]; Mondini, Juliana Nazatto [UNESP] (Federal Univ Ceara, 2021)
We demonstrate the development of language politics that enable indigenous education actions based on native languages. We discuss about studies of minority languages lexicon, such as Brazilian indigenous languages, the relevance of specialized lexicon research, which contributes to terminographic and lexicographic works. Taking into account the Ethnographic Terminology proposal (FARGETTI, 2019), the culinary field is focused among Juruna from the Xingu Indigenous Territory, Mato Grosso, and how its treatment in terminological vocabulary can contribute to intercultural bilingual education and registration of an important part of a Brazilian Tupi culture. For this, a specific fieldwork methodology is necessary, with a dialogue between sciences: that of the linguistic researcher and that of the indigenous specialist in an area of knowledge. Thus, a discussion of entry, with its subentries, prepared by Mondini (2014) is presented, in comparison with an entry in lexicographic work on other Brazilian indigenous language, which allows a contribution to Lexical Studies and its use in teaching.
Keywords: Indigenous language dictionary; Education; Etnographic Terminology